2006
DOI: 10.1007/s10640-006-9051-x
|View full text |Cite
|
Sign up to set email alerts
|

‘Adopt a Hypothetical Pup’: A Count Data Approach to the Valuation of Wildlife

Abstract: The willingness to pay (WTP) for a coyote conservation program is estimated using a novel payment-vehicle, based on how many ‚problem’ coyotes respondents would be willing to sponsor for a year. This hypothetical scenario mimics an increasingly popular type of actual market. Data from a phone survey conducted in Prince Edward Island are analyzed using count data models that consider different processes explaining zero responses and the level of positive responses. This is particularly important in the case of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 43 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…Ecological economists have proposed that irreducible value conflict is unavoidable and that only practical judgment formulated by deliberation provides an appropriate means for rational comparison (Martinez-Alier et al 1998;Isacs et al 2021). Furthermore, people may find it hard to understand biodiversity and ecosystems (Nunes et al 2001;Christie et al 2006;Hanley et al 2015), often do not have clearly pre-formed values (Kenter et al 2016c), and may themselves prefer values to be expressed through group deliberation, to shape decisions under societal perspectives rather than that of individual consumers (Sagoff 1998;Ward 1999;Shapansky et al 2003;Martinez-Espineira 2007;Bunse et al 2015;Lienhoop et al 2015;Kenter et al 2016b;Orchard-Webb et al 2016).…”
Section: Value Pluralitymentioning
confidence: 99%
“…Ecological economists have proposed that irreducible value conflict is unavoidable and that only practical judgment formulated by deliberation provides an appropriate means for rational comparison (Martinez-Alier et al 1998;Isacs et al 2021). Furthermore, people may find it hard to understand biodiversity and ecosystems (Nunes et al 2001;Christie et al 2006;Hanley et al 2015), often do not have clearly pre-formed values (Kenter et al 2016c), and may themselves prefer values to be expressed through group deliberation, to shape decisions under societal perspectives rather than that of individual consumers (Sagoff 1998;Ward 1999;Shapansky et al 2003;Martinez-Espineira 2007;Bunse et al 2015;Lienhoop et al 2015;Kenter et al 2016b;Orchard-Webb et al 2016).…”
Section: Value Pluralitymentioning
confidence: 99%
“…As regards the first and second point, behavioral literature recognises that values need not be preformed (i.e. existing as a priori ideas) but constructed through formal or informal deliberation (Shapansky et al 2003;Kenter et al 2016b,d) to shape decisions under societal perspectives rather than that of individual consumers (Lienhoop et al 2015;Martinez-Espineira 2007;Orchard-Webb et al 2016). As regards the third point, Arrow (1950) showed that there is "no logically infallible way to aggregate the preferences of diverse individuals"…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Bilgic and Florkowski (2007) apply a hurdle negative binomial model to estimate the demand for bass fishing in the southeastern United States. Martinez-Espineira (2007) employs zero-inflated models to estimate the willingness-to-pay for a coyote conservation program. Hurdle count models have also been used in other areas of research.…”
Section: Estimation Strategymentioning
confidence: 99%